Implementation of Project Based Learning in Islamic Religious Education: An Effort to Create a Generation with Islamic Character - Fahmi, Ryan; Azmaliah, Azmaliah; Jamna, M. Reza; Heryadi, Heryadi (Yayasan Rahmat Islamiyah, 2025)
This study aims to describe the implementation of the Project Based Learning (PJBL) model in Islamic Religious Education (IRE) and its role in fostering a generation with Islamic character. The research employed a qualitative approach using observation, interviews, and documentation techniques. The findings reveal that the application of PJBL in IRE enhances students’ active participation, creativity, and collaborative skills in completing learning projects oriented toward Islamic values. Moreover, PJBL proved effective in instilling religiosity, responsibility, cooperation, and honesty among students. Therefore, PJBL can serve as a relevant learning strategy to shape a generation with strong Islamic character in accordance with contemporary challenges.